2 (7X+2)+12(X+1)=2
-2(X-3)=18
3(2X-5)=9-2X
5(Y-3)=2Y+3
8X-16=6X-10
Soluções para a tarefa
Respondido por
0
2 (7X+2)+12(X+1)=2
14x+4+12x+1=2
14x+12x=2-1-4
26x=-3
x=-3/26
-2(X-3)=18
-2x+6=18
-2x=18-6
-2x=2.(-1)
2x=-2
x=-2/2
x=-1
3(2X-5)=9-2X
6x-15=9-2x
6x+2x=9+15
8x=24
x=24/8
x=3
5(Y-3)=2Y+3
5y-15=2y+3
5y-2y=3+15
3y=18
y=18/3
y=6
8X-16=6X-10
8x-6x=-10+16
2x=6
x=6/2
x=3
14x+4+12x+1=2
14x+12x=2-1-4
26x=-3
x=-3/26
-2(X-3)=18
-2x+6=18
-2x=18-6
-2x=2.(-1)
2x=-2
x=-2/2
x=-1
3(2X-5)=9-2X
6x-15=9-2x
6x+2x=9+15
8x=24
x=24/8
x=3
5(Y-3)=2Y+3
5y-15=2y+3
5y-2y=3+15
3y=18
y=18/3
y=6
8X-16=6X-10
8x-6x=-10+16
2x=6
x=6/2
x=3
Respondido por
0
2.(7x + 2) + 12.(x + 1) = 2
14x + 4 + 12x + 12 = 2
14x + 12x = 2 - 16
26x = -14
x = -14/26
x = -7/13
.
.
.
-2.(x - 3) = 18
-2x + 6 = 18
-2x = 18 - 6
-2x = 12
x = 12/-2
x = -6
.
.
.
3.(2x - 5) = 9 - 2x
6x - 15 = 9 - 2x
6x + 2x = 9 + 15
8x = 24
x = 24/8
x = 3
.
.
.
5.(y - 3) = 2y + 3
5y - 15 = 2y + 3
5y - 2y = 3 + 15
3y = 18
y = 18/3
y = 6
.
.
.
8x - 16 = 6x - 10
8x - 6x = -10 + 16
2x = 6
x = 6/2
x = 3
★Espero ter ajudado!
14x + 4 + 12x + 12 = 2
14x + 12x = 2 - 16
26x = -14
x = -14/26
x = -7/13
.
.
.
-2.(x - 3) = 18
-2x + 6 = 18
-2x = 18 - 6
-2x = 12
x = 12/-2
x = -6
.
.
.
3.(2x - 5) = 9 - 2x
6x - 15 = 9 - 2x
6x + 2x = 9 + 15
8x = 24
x = 24/8
x = 3
.
.
.
5.(y - 3) = 2y + 3
5y - 15 = 2y + 3
5y - 2y = 3 + 15
3y = 18
y = 18/3
y = 6
.
.
.
8x - 16 = 6x - 10
8x - 6x = -10 + 16
2x = 6
x = 6/2
x = 3
★Espero ter ajudado!
Perguntas interessantes
Saúde,
11 meses atrás
Português,
11 meses atrás
Português,
11 meses atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Ed. Física,
1 ano atrás